MODEL OF BUSINESS PARTICIPATION IN DIGITAL TRANSFORMATION - DVORNYK, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The processes occurring in the modern market environment have led to the acceleration of digital solutions adoption, which streamline the operations of business structures through the implementation of technological platforms, optimize costs, and enhance the quality of professional activities. Nowadays, the business model of a digital platform can be defined by a number of attributes, the main of which are: aggregation of supply and demand; utilization of data for value creation; adaptation of technological innovations to the regional market, and increasing operational efficiency. In order to maximize the benefits of platform utilization, the article proposes three participation models in the digital transformation of enterprises: partnership, hybrid model, and independent platform assembly. The considered models, in perspective, will allow business structures to expand cooperation with market counterparts for mutual benefit and further support of sustainable growth of the digital economy. Such participation models in the digital transformation of enterprises have the potential to create new opportunities for businesses in the era of digital technologies. Partnership enables collaboration with other companies for joint development and utilization of digital tools. The hybrid model combines the advantages of in-house development and collaboration with partners, significantly expanding the possibilities of implementing digital innovations. Independent platform assembly provides businesses with full control over the development of digital tools and the ability to adapt them to specific company needs. However, successful digital transformation requires not only choosing the appropriate participation model but also actively implementing digital strategies and improving business processes. It is important to integrate digital solutions into all aspects of enterprise activity to ensure their effectiveness and maximum impact on business performance. Thus, choosing the right participation model in digital transformation and its successful implementation can be a key factor in achieving competitive advantages and ensuring sustainable growth in the digital era.